A single-plasmid-based, easily curable CRISPR/Cas9 system for rapid, iterative genome editing in Pseudomonas putida KT2440 - Qifeng Wen; JinJin Chen; Jin Li; Ida Putu Wiweka Dharmasiddhi; Maohua Yang; Jianmin Xing; Yilan Liu (Microbial Cell Factories)
Abstract Background Pseudomonas putida KT2440, a non-pathogenic soil bacterium, is a key platform strain in synthetic biology and industrial applications due to its robustness and metabolic versatility. Various systems have been developed for genome editing in P. putida, including transposon modules, integrative plasmids, recombineering systems, and CRISPR/Cas systems. However, rapid iterative genome editing is limited by complex and lengthy processes. Results We discovered that the pBBR1MCS2 plasmid carrying the CRISPR/Cas9 module could be easily cured in P. putida KT2440 at 30 oC. We then developed an all-in-one CRISPR/Cas9 system for yqhD and ech-vdh-fcs deletions, respectively, and further optimized the editing efficiency by varying homology arm lengths and target sites. Sequential gene deletions of vdh and vanAB were carried out rapidly using single-round processing and easy plasmid curing. This system’s user-friendliness was validated by 3 researchers from two labs for 9 deletions, 3 substitutions, and 2 insertions. Finally, iterative genome editing was used to engineer P. putida for valencene biosynthesis, achieving a 10-fold increase in yield. Conclusions We developed and applied a rapid all-in-one plasmid CRISPR/Cas9 system for genome editing in P. putida. This system requires less than 1.5 days for one edit due to simplified plasmid construction, electroporation and curing processes, thus accelerating the cycle of genome editing. To our knowledge, this is the fastest iterative genome editing system for P. putida. Using this system, we rapidly engineered P. putida for valencene biosynthesis for the first time, showcasing the system’s potential for expanding biotechnological applications.